2013
DOI: 10.1007/s00464-013-2950-3
|View full text |Cite
|
Sign up to set email alerts
|

A prospective assessment of renal oxygenation in children undergoing laparoscopy using near-infrared spectroscopy

Abstract: Renal hypoxia does not occur during laparoscopic surgery in children if the minimum age-appropriate intra-abdominal pressures are used. Alternative causes must account for the oliguria and anuria demonstrated in children undergoing laparoscopy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 44 publications
0
17
0
Order By: Relevance
“…Little is known about the relevance of NIRS in the simultaneous monitoring of cerebral and abdominal or renal perfusion in neonatal digestive surgeries (1316). Giliberti et al reported and summarized the results of a study on the application of NIRS in neonatal cardiac and digestive surgeries, on its future possibilities and its relevance on perfusion and oxygenation monitoring during these surgeries and during anesthesia.…”
Section: Introductionmentioning
confidence: 99%
“…Little is known about the relevance of NIRS in the simultaneous monitoring of cerebral and abdominal or renal perfusion in neonatal digestive surgeries (1316). Giliberti et al reported and summarized the results of a study on the application of NIRS in neonatal cardiac and digestive surgeries, on its future possibilities and its relevance on perfusion and oxygenation monitoring during these surgeries and during anesthesia.…”
Section: Introductionmentioning
confidence: 99%
“…Although there are several studies assessing abdominal saturation with NIRS in various diseases, there are no studies evaluating this during CPR [9,11,[16][17][18][19]]. One animal model study performed to determine abdominal ischemia in patients with shock compared invasive techniques with NIRS and reported that NIRS was a good means of detecting abdominal ischemia.…”
Section: Discussionmentioning
confidence: 99%
“…Oxygenation of other organs is as important as that of the brain during CPR. Near-infrared spectrophotometry can assess myocardial, hepatic, and intestinal saturation by measuring tissue saturation [9][10][11]. Although cardiac activity can be evaluated with echocardiography, a noninvasive technique, invasive methods such as catheterization need to be used to assess abdominal oxygenation.…”
Section: Introductionmentioning
confidence: 99%
“…However, peritoneal gas insufflation during laparoscopy may lead to possibly harmful cardiovascular and respiratory alterations that could possibly be detrimental for the patient. [5678910131416] PP exerts its effects on organ systems primarily via physical pressure on those systems and secondly through the systemic absorption of CO 2 across the peritoneum and into the bloodstream.…”
Section: Discussionmentioning
confidence: 99%